Rasgos identitarios de los sujetos migrantes en las crónicas ecuatorianas Permiso de residencia, de María Fernanda Ampuero y El color de los sueños, de Annabelle Chimbo - Malla Armijos, Jason Henry (2022)
This research analyzes the identity traits of Ecuadorian migrant subjects in the emigration chronicles of the writers María Fernanda Ampuero and Annabell Chimbo, through the identification of personal identity and the assessment of the identity crisis of Ecuadorian migrants in the chronicles. The corpus used in the research are the books of chronicles Permiso de residencia (2013) and El color de los sueños (2016) that recount experiences of migrants in their journey from Ecuador to other destinations, such as the United States and Spain. The research applies a qualitative approach. For the analysis of the data, the thematic method was used, which Braun and Clarke, (2006) mention that it is a thorough reading and rereading for a better understanding of the subject of analysis. As well as the content method, which is a data collection instrument used to interpret the texts in a systematic, objective, replicable and valid way. As well as personal reflection, this serves to reveal and evidence the feelings and conceptions of Ecuadorian migrants with the purpose of promoting reflection on the experiences they had in the migration process. The results show that the migrant subject presents three categories of personal identity: the ontological, the psychosocial and the ecosystemic, the same that configure the construction of their identity by the environment in which they develop. The assessment of the identity crisis showed us a replantation of the way of seeing things, their work, their way of socializing, and how it permanently affects their performance at work, and affects their health. Therefore, it is concluded that identity is a process that links several fields, personal, psychological, emotional, family, territorial, anthropological, psychosocial, political, economic, and shows that the fact of moving from one place to another makes us change the vision of what we are and what we have been in a certain territory; the way we saw the world takes a resounding change to find ourselves outside an area known to us. keywords: Personal identity, ontological identity, migration identity, migration and literature